Pabrikasi Unit Kontrol Berbasis Web pada Smarthome System untuk Pengoperasian Pintu Gerbang - Lucky Hardian; Arief Goeritno (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
A control unit based-on web in smarthome system has been designed and constructed. The control unit can be integrated into the smarthome system platform for gate operation via a smartphone. The research objectives, namely (i) integration of hardware and availability of raw files for applications, (ii) programming for control unit, and (iii) availability of control unit and implementation of validation tests. The result of integration is a form of successful hardware handshaking. The programming result is a form of successful software handshaking, including (i) a flowchart-based algorithm, while the syntax structure is based on the Arduino IDE, (ii) the comfiling and uploading stages of the syntax structure to the Arduino UNO R3 module, including the process online control based on RemoteXY version 4.5.1 via a web browser, and (iii) uploading files from personal computers and smartphones based on Android. The availability of the control unit physical building for the validation test process is the achievement of handshaking in hardware and software, in the form of performance measurement of the control unit with 3 (three) kinds of observations, namely (i) “open”, (ii) “close”, or (iii) lock/unlock state. In general, it is concluded that the web-based control unit on the smarthome system for gate operation can function and perform according to plan.